(3QSGdI aj Yde Gdcas - (3CHh YeQ GdcfOj , CHh jYbhH Hf eMeO Hf ESMGb GdcfOj, GdcfOj,J (B355 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3hHYO Efi hLOJ UMjaI ajgG ef Yde Gdca CTjGA LQHJ CcKQgG s
(3BNQgG (B:s
(3aEf GYJQVJ SMGHI UaQGA Ch fehTI eY GdLRGJ adGHO ddeQcH Cf JYWH hJgdc ChJgRe s
(3gPg GdQSGdI hLggG GdeDda Edi jMji Hf eGShe NGOe GdeYJUes
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B142s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B140 s
Keywords: (3GdaQGSIs